Analisis Kinerja Keuangan dan Pelayanan dengan Kemandirian Rumah Sakit di RSUD Dr.Abdoer Rahem Situbondo - Mentari Candrasari; Taufik Kurrohman; Nining Ika Wahyuni (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This study aims to analyze the financial performance and service or the dr. Abdoer Rahem hospital that implement regional public service agency since 2009. This study included a quantitive research with time series method. The data used is secondary data collected through the financial statements and management report hospital. Financial performance is measured by financial ratios of liquidity ratio, solvency ratio, and profitability ratio. Meanwhile, service performance is measured by six indicators, namely: Bed Occupancy Rate (BOR), Turn Over Interval (TOI), Bed Turn Over (BTO), Average Length of Stay (ALOS), Gross Date Rate (GDR), dan Net Date Rate (NDR). The study’s hypotheses were tested using pearson corerelation. The results showed that financial performance is measured by the solvency ratio is statistically proven to correlate strongly with the cost recovery rate and level of independence. Service performance as measured by BTO has a strong correlation with the level of independence.Keywords: financial performance, service performance, cost recovery rate, and level of independence